Plant Growth Promoting and Abiotic Stress Tolerant Chickpea (Cicer arietinum L.) Rhizobial Isolates from Some Areas of South Wollo Zone, Ethiopia - Asmamaw Menelih; Faris Hailu; Mussa Adal (Advances in Agriculture)
Chickpea (Cicer arietinum L) is an important pulse crop prized for its high protein content and is grown as a food source worldwide, including Ethiopia. However, the yield of chickpea is low due to low soil fertility and the ever-changing abiotic stresses. Therefore, this study aimed at isolation, characterization, and selection of chickpea rhizobia effective in their nitrogen fixation and abiotic stress tolerance potential. As a result, 150 nodule samples were collected from three districts of chickpea-producing areas in South Wollo. The nodules were crushed, and the rhizobia were isolated and characterized by using standard microbiological procedures. Based on the presumptive tests conducted, 103 (68.7%) of the rhizobial isolates were tentatively categorized as Rhizobium species. Regarding phosphate solubilization, only 48 (46.7%) solubilized phosphate with a solubilization index ranging from 2.1 to 2.7 mm. Twenty-four (50%) of the isolates were found to be hydrogen cyanide producers. Among the rhizobial isolates tested under greenhouse conditions, 37 (77.1%) of them induced nodulation on their host plant (chickpea). Their symbiotic effectiveness evaluation test confirmed that 16(47.1%), 6(17.6%), 26.47%, and 3(8.8%) were highly effective, effective, low effective, and ineffective, respectively. Of the authenticated rhizobial isolates, 12 (35.5%) of them, including WuCR-15, 16, 17, 18, 19, 20, 23, 30, 31, 32, 36, 38, and 48, accumulated higher shoot dry matter than the positive control. Isolates WuCR- 11, 17, and 36 showed resistance to low and high extreme abiotic stresses of pH, temperature, and salt. Consequently, rhizobial isolates, WuCR- 11, 17, and 36, which were effective and competent in all the tested parameters, were recommended as good rhizobial candidates for applications under greenhouse and field conditions.